Improving Mathematic Communications Skill by Using Mathematic Realistic Setting Cooperative Learning with Student Teams Achievement Divisions (STAD) type - Tri Novita Irawati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2017)
Mathematical communication of students is the ability of students to communicate both orally and in writing in the process of learning mathematics. The ability of students' mathematical communication can increase if there is a change in learning one of them through application  of Realistic Mathematics learning with STAD Type Cooperative Setting. This type of research is a classroom action research. Data analysis is done qualitatively and quantitatively to the ability of oral and written communication of students. Based on the results of analysis on the cycle I and II students' communication skills in cycle I and cycle II has increased. Student's oral communication ability in cycle I got the average score of 9.17 with the category of "Good Enough" and on cycle II increased with category "Very Good" and obtained average score 12.62. The students' writing communication skills also improved. In the first and second cycles of students' writing communication skills increased with the category of "Very Good" and obtained score 63.76 and in cycle II increased with the category "Very Good" and obtained an average score of 82.18. Based on these things then this learning can be used as an alternative in learning mathematics to improve the ability of oral and written communication of students.Key words: PMR, STAD, communication skill